Melampaui Batas Cahaya: Kajian Tentang Fotosintesis Tumbuhan dalam Tafsir Bil Ilmi - Rosadi, Nora Juwita D.; Hakim, Lukman Nul (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This article explores the harmonious marriage between modern science and Quranic insights in the understanding of plant photosynthesis. Titled "Beyond the Limits of Light: A Study of Photosynthesis in Tafsir Bil Ilmi," it will discuss how the concept of tafsir bil ilmi opens the door to understanding the phenomenon of photosynthesis through the lens of science. This study focuses on a critical investigation of the process of plant photosynthesis in the context of science-based tafsir. Through an understanding of tafsir bil ilmi, this article explores how Quranic verses can be interpreted in terms of modern scientific concepts related to photosynthesis. The research includes a detailed review of the stages of photosynthesis, exposing the linkages between Quranic verses and the scientific principles underlying this phenomenon. This article aims to present a more in-depth view of the rich meanings found in the Quran, particularly in the context of the wonders and design intelligence in the process of photosynthesis. By weaving together science and religious views, this article invites readers to see photosynthesis as evidence of the wisdom of creation, evoking a deeper understanding of the relationship between nature and divine revelation. Thus, "Beyond the Limits of Light" is not just a scientific study, but also an attempt to harmonize knowledge and spirituality in understanding the life around us.